Women's views of continuity of information provided during and after pregnancy: A qualitative interview study. (15th April 2019) - Olander, Ellinor K.; Aquino, Maria Raisa Jessica (Ryc); Chhoa, Celine; Harris, Erica; Lee, Suzanne; Bryar, Rosamund M.
Abstract: Straightforward transfer of care from pregnancy to the postpartum period is associated with health benefits and is desired by women worldwide. Underpinning this transfer of care is the sharing of information between healthcare professionals and the provision of consistent information to women. In this qualitative study, two aspects of continuity of information were examined; first the information passed on from midwife to health visitor regarding a woman and her baby before the health visitor meets the woman postnatally and second, the consistency of information received by women from these two healthcare professionals (the main healthcare providers during and after pregnancy in England). To be eligible for the study, women had to have had a baby in England within 12 months prior to the interview. Participants also needed to be able to read and speak English and be over 18 years old. Recruitment of participants was via word of mouth and social media. Twenty‐nine mothers were interviewed of whom 19 were first time mothers. The interviews took place in the summer and autumn of 2016 and were transcribed verbatim and analysed using Framework Analysis. Two overarching themes were identified: not feeling listened to and information inconsistencies. Women reported little experience of midwives and health visitors sharing information about their care, forcing women to repeat information. This made women feel not listened to and participants recommended that healthcare professionals share information; prioritising information about labour, mental health, and chronic conditions. Women had mixed experiences regarding receiving information from midwives and health visitors, with examples of both consistent and inconsistent information received. To avoid inconsistent information, joint appointments were recommended. Findings from this study clearly suggest that better communication pathways need to be developed and effectively implemented for midwives and health visitors to improve the care that they provide to women.